THE INTERIOR DESIGN OF A MUSIC SCHOOL FOR PERSONS WITH VISION IMPAIRMENT WITH THE CONCEPT OF LANDMARK PERCEPTION IN SURAKARTA, INDONESIA - W Ranta Cosynala; Ahmad Fajar Ariyanto (Pendhapa, 2020)
The Law of the Republic of Indonesia, article 5, paragraphs 1 and 2 concerning the education system, states that every citizen has the same right to obtain a good quality education. Citizens who have physical, emotional, mental, intellectual, and social disabilities are entitled to special education, including vision impairment. One of those people with vision impairment skills is their music expertise by maximizing touch and the sense of hearing. This work aims to realize the Landmark Perception concept by applying dynamic repetition by visualizing the repetition of several elements, such as line, shapes, textures, colors, dimensional gradations, shape gradations, and circulation patterns. These work results are the interior designs for the main facilities, including vocal classrooms, guitar classrooms, Violin classrooms, drum classrooms, piano classrooms, concert halls, and some supporting facilities such as cafeterias and libraries. The results of this work can be a reference for interior designers in designing interiors in a contemporary style based on the needs of people with vision impairment.